RSI (Relative Stress Index) Based Cognitive Measurement Model with NASA-TLX, RSME (Rating Scale Mental Effort Index) and GHQ-12 Methods (Case Study: Sales Marketing): Model Pengukuran Kognitif Berbasis RSI (Relative Stress Index) dengan Metode NASA-TLX, RSME (Rating Scale Mental Effort Index) dan GHQ-12 (Studi Kasus: Sales Marketing) - Rizal Adamy, Muhammad (Universitas Muhammadiyah Sidoarjo, 2022)
Methods Currently, business competition between manufacturing companies in Indonesia is increasingly diverse. There are many companies that have the same type of business but have their respective advantages of quality products offered at competitive prices. This quality is one of the factors to measure the level of customer satisfaction. PT. Loscam is a foreign company engaged in wood pallet rental services. Sales marketing is the most influential part of a company’s revenue. The Covid-19 pandemic caused some companies to reduce the number of employees or workers, resulting in workers being laid off in an effort to prevent the spread of the disease. Maintain their business and of course to reduce losses due to Covid-19. At PT. Loscam Surabaya. Sales Marketing is the division that is tasked with conducting marketing activities directly or indirectly to customers and conducting market analysis for promotion so that goods (pallets) can be rented by customers, so that efforts become greater to find new customers. The purpose of this study was to determine the relationship between work stress and work stress using Relative Stress Index method, to determine mental load using NASA TLX method, to determine mental load based on level of effort expended using RSME, and to determine mental load based on psychiatry using GHQ method -12. The RSI results showed that there was no significant relationship between job type and work stress. That is the work pressure experienced by Sales Marketing at PT. Loscam is likely to be influenced by other things not contained in the job description in the RSI table. For NASA TLX, the score obtained by respondent 1 was 90 (very high classification), respondent 2 with a value of 70.67 (high), respondent 3 with a value of 78.67 (high), and respondent 3 with a value of 86 (very high). The RSME value obtained by respondent 1 was 136.67 (business category produced was very large), respondent 2 was 70.70 (effort spent was quite large), respondent 3 had a value of 80 (effort spent was large), and respondent. 4 with a value of 135 (the effort expended is enormous). For the GHQ-12 value, the level of stress occurred in respondent 2 with a score of 17 (low score), then respondent 1 (score 2), respondent 3 (score 6), and respondent 4 (score 10) in the non-stress category.